Association of TNFAIP8 gene polymorphisms with cancer risk in Chinese population. (7th July 2022) - Gao, Xueren; Xiong, Chengju; Wang, Dongbo; Yang, Jiaxin; Jia, Wendi; Yang, Lingmei; Wang, Xinyu; Zhao, Yining
Abstract: As TNFAIP8 plays an important role in the development of cancer, several studies have analyzed the relationship between potential functional polymorphic loci of the TNFAIP8 gene and cancer risk. However, some results were inconsistent. Therefore, the current study aims to systematically assess the relationship between these genetic polymorphisms and cancer risk using a meta-analysis approach. Relevant studies were obtained from CNKI, Embase, Web of Science, and PubMed databases. RevMan software was used to conduct data analysis. The combined analysis containing four studies with 2786 cancer patients and 2550 control individuals indicated that rs11064 polymorphism was not associated with cancer risk. The pooled analysis containing three studies with 950 cancer patients and 1036 control individuals showed that rs1045241 polymorphism was associated with cancer risk in the heterozygous model (CT vs. CC: OR = 1.34, 95%CI = 1.10‐1.62, Pz =0.003) and dominant model [(TT + CT) vs. CC: OR = 1.38, 95% CI = 1.15-1.66, Pz =0.0006], but not in other models. The pooled analysis containing two studies 436 cancer patients and 479 control individuals showed that rs1045242 polymorphism was associated with cancer risk in the heterozygous model (AG vs. AA: OR = 1.52, 95%CI = 1.14-2.03, Pz =0.005), dominant model [(GG + AG) vs. AA: OR = 1.56, 95% CI = 1.18-2.07, Pz =0.002] and allelic model (G vs. A: OR = 1.48, 95%CI = 1.16-1.90, Pz =0.002). In conclusion, the current findings suggest that the rs1045241 and rs1045242 polymorphisms located on the TNFAIP8 gene were associated with cancer risk in Chinese population, and may serve as valuable genetic susceptibility markers.